2022
DOI: 10.1080/20964129.2022.2052762
|View full text |Cite
|
Sign up to set email alerts
|

Responses of grazing households to different levels of payments for ecosystem services

Abstract: Introduction Payments for Ecosystem Services (PES) programs have been implemented globally to protect ecosystems while securing the well-being of affected people. Reasonable payment standards are key to successful PES programs. Although some approaches are available for determining payment standards, few studies have applied them for grassland conservation with location indicators and socioeconomic contexts properly considered. Methods Using China’s fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…A study by Li et al (2022) on grassland ecological compensation programs found significant differences in herders' policy satisfaction influenced by factors such as household income, payment cognition, and the size of household-owned grasslands [13]. Another study by Shen et al (2022) on herders in Damao County, Inner Mongolia, showed that householders who were older and better educated, and who had lower incomes from livestock, larger grasslands and weaker social connections were more likely to participate in ecological compensation programs [28]. In southern China, forest ecosystems are the focus for ecological compensation projects.…”
Section: Rural Households' Attitudes and Influencing Factorsmentioning
confidence: 99%
“…A study by Li et al (2022) on grassland ecological compensation programs found significant differences in herders' policy satisfaction influenced by factors such as household income, payment cognition, and the size of household-owned grasslands [13]. Another study by Shen et al (2022) on herders in Damao County, Inner Mongolia, showed that householders who were older and better educated, and who had lower incomes from livestock, larger grasslands and weaker social connections were more likely to participate in ecological compensation programs [28]. In southern China, forest ecosystems are the focus for ecological compensation projects.…”
Section: Rural Households' Attitudes and Influencing Factorsmentioning
confidence: 99%
“…Social and economic issues, such as limited access to markets and input resources, weak governance and lack of knowledge around alternative production technologies, frequently constrain the options available to communities in degraded landscapes [ 27 ], such that ecological restoration may encourage local investment and lead to employment opportunities under adaptive management combined with socioeconomic development [ 28 ]. In addition, the costs of improving ecosystem service delivery in an ecological restoration project may be considered, at least partially, as leverage for local sustainable livelihoods [ 29 , 30 ]. It should be noted that the contribution of ecological restoration to markets and livelihoods is not unidirectional, as the issues in sustainable livelihoods and socioeconomic development also drive decision-making in ecological restoration.…”
Section: Relationship Between Ecological Restoration and Sustainable ...mentioning
confidence: 99%
“…First, the payment standard is low. With the improvement of the payment level, the enthusiasm of the herder households to reduce livestock herd counts will also increase (Shen et al, 2022). Second, supervision is weak.…”
Section: Introductionmentioning
confidence: 99%